Identification of MFRP and the secreted serine proteases PRSS56 and ADAMTS19 as part of a molecular network involved in ocular growth regulation. - Swanand Koli; Cassandre Labelle-Dumais; Yin Zhao; Seyyedhassan Paylakhi; K Saidas Nair (PLoS Genetics)
Precise regulation of ocular size is a critical determinant of normal visual acuity. Although it is generally accepted that ocular growth relies on a cascade of signaling events transmitted from the retina to the sclera, the factors and mechanism(s) involved are poorly understood. Recent studies have highlighted the importance of the retinal secreted serine protease PRSS56 and transmembrane glycoprotein MFRP, a factor predominantly expressed in the retinal pigment epithelium (RPE), in ocular size determination. Mutations in PRSS56 and MFRP constitute a major cause of nanophthalmos, a condition characterized by severe reduction in ocular axial length/extreme hyperopia. Interestingly, common variants of these genes have been implicated in myopia, a condition associated with ocular elongation. Consistent with these findings, mice with loss of function mutation in PRSS56 or MFRP exhibit a reduction in ocular axial length. However, the molecular network and cellular processes involved in PRSS56- and MFRP-mediated ocular axial growth remain elusive. Here, we show that Adamts19 expression is significantly upregulated in the retina of mice lacking either Prss56 or Mfrp. Importantly, using genetic mouse models, we demonstrate that while ADAMTS19 is not required for ocular growth during normal development, its inactivation exacerbates ocular axial length reduction in Prss56 and Mfrp mutant mice. These results suggest that the upregulation of retinal Adamts19 is part of an adaptive molecular response to counteract impaired ocular growth. Using a complementary genetic approach, we show that loss of PRSS56 or MFRP function prevents excessive ocular axial growth in a mouse model of early-onset myopia caused by a null mutation in Irbp, thus, demonstrating that PRSS56 and MFRP are also required for pathological ocular elongation. Collectively, our findings provide new insights into the molecular network involved in ocular axial growth and support a role for molecular crosstalk between the retina and RPE involved in refractive development.